Interpretation of Interreligious Marriages From the Perspective of Tafsir Ahl al-Kitab: A Comparative Study of Classical and Contemporary - Jamal, Khairunnas; Akbar, Ali; Novendri S, Mochammad; ., Aslati; ., Agustiar; ., Rahman (Journal of Ecohumanism, 2025)
This study discusses the interpretation of interreligious marriage in the perspective verse of the Ahl al-Kitab in comparative study of classical and contemporary interpretation. This study aims to identify how mufasir of various eras understood and applied the verses that allowed marriage between Muslim men and women of Ahl al-Kitab, as well as how social developments and modern religious perspective influencing these interpretations. Different marriages provide a perspective evolution of interreligious marriage in the marriage verse of the Ahl al-Kitab. This research discusses the transformation of classical and contemporary interpretations related to interreligious marriage in the practice of marriage in the modern era. This is a library research with a literature study approach and the methodology used was comparative. The data related to this study were collected through primary data and secondary data. The data is presented with technical analysis of muqaranah and content analysis. The results of the study stated that classical interpretation generally prioritizes the legality aspect with little attention to the long-term impact, while contemporary interpretation emphasizes the importance of social context and challenges faced in modern life. The shifting reflect a transformation in religious thinking, where the moral aspect and stability of faith in the household are the main concerns. Interreligious marriage in Islam cannot be hidden because it was legalized in the salaf era, the classical interpretation highlights the possibility of marriage to the ahlul from the group of Dzimmi or Harbiy. Meanwhile, there are pros and cons about its possibilities and haram by the view of contemporary interpretation, because the different ways in defining the terminology of the Ahl al-Kita.